Peran dan Strategi Public Relations Dalam Membangun Citra Perusahaan Perbankan - Putri, Tabitha Stefani; Wijaya, Lina Sinatra (Jurnal Pustaka Komunikasi, 2024)
Image is one of the most important parts of the company that must be continuously built and maintained. Realizing this, public relations of PT Bank Kalteng made various efforts to build a positive corporate image. This study aims to determine the role and strategy of public relations (PR) in building corporate image. This study uses a descriptive qualitative using indepth interviews and observations as data sources. The collected data were analyzed using qualitative analysis methods, consisting of data reduction, data presentation, and conclusion drawing. Then for data validation, this research uses triangulation. The triangulation used is source triangulation and method triangulation. The study results show that PR PT Bank Kalteng plays the role of Expert Prescriber, Communication Facilitator, Problem Solving Process Facilitator, and Communication Technician in building a corporate image. In addition, The PR of the bank has carried out a strategy to improve the banking image through three stages: to secure understanding, establish acceptance, and motivate action.